2020
DOI: 10.26633/rpsp.2020.78
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of leptospirosis outbreaks worldwide, 1970–2012

Abstract: Objective. This review describes the geographic and temporal distribution of, detection methods for, and other epidemiological features of published leptospirosis outbreaks, with the aim of informing efforts to standardize outbreak-reporting practices. Methods. We conducted a systematic review of leptospirosis outbreaks reported in the scientific literature and ProMED during 1970–2012. Predefined criteria were used to identify and classify outbreaks and a standard form was used to extract information. Results.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
60
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 42 publications
3
60
0
3
Order By: Relevance
“…Several outbreaks have been reported in urban areas around the world after heavy rainfall and flood events, which bring the bacteria and their animal hosts in closer contact with humans, including in Guyana, India, Indonesia, Italy, Philippines and Malaysia [12][13][14][15][16][17]. A systematic review of leptospirosis outbreaks identified that out of 318 leptospirosis outbreaks from 1970 to 2012, among the ones that had information about the settings, 16% occurred in urban and 15% in rural areas [18]. Endemic transmission of leptospirosis is reported in rural areas and is frequently associated with specific occupational groups therein, as described in Argentina, Brazil, Nicaragua, Lao, Mexico, New Zealand and Sri Lanka [19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Several outbreaks have been reported in urban areas around the world after heavy rainfall and flood events, which bring the bacteria and their animal hosts in closer contact with humans, including in Guyana, India, Indonesia, Italy, Philippines and Malaysia [12][13][14][15][16][17]. A systematic review of leptospirosis outbreaks identified that out of 318 leptospirosis outbreaks from 1970 to 2012, among the ones that had information about the settings, 16% occurred in urban and 15% in rural areas [18]. Endemic transmission of leptospirosis is reported in rural areas and is frequently associated with specific occupational groups therein, as described in Argentina, Brazil, Nicaragua, Lao, Mexico, New Zealand and Sri Lanka [19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Leptospirosis is a bacterial zoonotic disease of worldwide distribution, potentially lethal and capable of causing epidemic outbreaks in human and domestic animal populations [ 1 , 2 ]. Dogs can act as an important source of infection for humans and other mammals, as they are able to excrete the pathogen into the environment via urine and other body fluids [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Leptospirosis is a bacterial zoonotic disease of worldwide distribution, potentially lethal and capable of causing epidemic outbreaks in human and domestic animal populations (1,2). Dogs can act as an important source of infection for humans and other mammals, as they are able to eliminate the pathogen into the environment via urine and other body uids (3).…”
Section: Introductionmentioning
confidence: 99%